Development of Interactive E-LKPD Based on Problem Based Learning for Grade X of Vocational School - Aprianah, Betty; Susila, Heni Rita; Pebriantika, Leni (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aims to develop an interactive Electronic Student Worksheet (E-LKPD) based on Problem-Based Learning (PBL) for teaching arithmetic sequences in Grade X vocational high school. The study employed a Research and Development (R&D) approach using the ADDIE model integrated with Tessmer’s formative evaluation. The development process involved stages of analysis, design, development, implementation, and evaluation, followed by expert validation and user testing. The results showed that the developed E-LKPD achieved high validity and practicality. Expert validation indicated that the product was highly feasible, with content validity reaching 97.19%, media quality 90.83%, and instructional design 85.42%. The product trials also demonstrated very high practicality, with scores of 97.27% in one-to-one evaluation, 92.11% in small group evaluation, and 93.96% in field testing. These findings indicate that the E-LKPD is valid, practical, and suitable for classroom implementation. The integration of PBL within the interactive E-LKPD effectively promotes student engagement, independent learning, and problem-solving skills. Therefore, the developed E-LKPD can serve as an innovative digital learning resource to support student-centered learning in vocational mathematics education.